Laboratory Simulation of Corrosion Damage in Reinforced Concrete - Altoubat, S.; Maalej, M.; Shaikh, Faiz (2016)
This paper reports the results of an experimental program involving several small-scale columns which were constructed to simulate corrosion damage in the field using two accelerated corrosion techniques namely, constant voltage and constant current. A total of six columns were cast for this experiment. For one pair of regular RC columns, corrosion was accelerated using constant voltage and for another pair, corrosion was accelerated using constant current. The remaining pair of regular RC columns was used as control. In the experiment, all the columns were subjected to cyclic wetting and drying using sodium chloride (NaCl) solution. The currents were monitored on an hourly interval and cracks were visually checked throughout the test program. After the specimens had suffered sufficient percentage steel loss, all the columns including the control were tested to failure in compression. The test results generated show that accelerated corrosion using impressed constant current produces more corrosion damage than that using constant voltage. The results suggest that the constant current approach can be better used to simulate corrosion damage of reinforced concrete structures and to assess the effectiveness of various materials, repair strategies and admixtures to resist corrosion damage.